Biased access? Exploring selection to advisory committees. (13th November 2014) - Rasmussen, Anne; Gross, Vlad
Abstract : The existing literature on bias in interest group access faces the challenge that there is often no clear benchmark for judging whether a given distribution of interest groups involved in policy making is biased. To tackle this challenge, we link two new data sets on registered European Union (EU) interest groups and membership of the advisory committees of the European Commission and examine the factors affecting selection to these committees. Our approach allows us to qualify the conclusions of the existing literature. We see that, even if business interests dominate advisory committees, they are not generally privileged over other group types in the selection processes and their degree of access varies considerably between policy areas. Instead, supranational interest groups enjoy selection privileges, which are particularly pronounced on permanent committees. Finally, we find some evidence that, even though lobbying budgets are important for getting access, their value varies across group types. In this way, our study has implications for future theory building on resource exchanges between interest group types and decision makers.